Implementasi Model Project Based Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Cahaya Dan Alat Optik - Dewi Nur Septiyana; Khaerus Syahidi; Eko Septi Mardi (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2023)
This study aims to improve students ' physics learning outcomes by using the learning model of Project Based Learning (PjBL). In this study using the method of classroom action research (PTK) conducted in 2 cycles where each there are four stages of planning (Planning), Action (Action), observation (Observation), and reflection (Reflection). The result of this research is the use of Project Based Learning (PjBL) learning model on light materials and optical devices can improve students ' physics learning outcomes. Cycle I has an average value of 11.36 and the average pretest posttet 40.40, increased in Cycle II is the average pretest 11.36 and the average posttest of 58.48. While the difference between the average value of posttest and pretest in the first cycle is equal to 29.04 and in the second cycle is equal to 47.12. From the results that have been obtained, it shows that there is an increase in the results of learning physics from cycle I and Cycle II.